New breeding grounds of Reticulitermes lucifugus (Rossi) (lsoptera Rhinotermitidae) in Lombardy (Italy) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two colonies of Reticulitermes lucifugus (Rossi) were found in the province of Varese (Lombardy, Italy), infesting 3 houses.
Keywords: mediterranean termite; termites; wood pests